Responses of successful local firms to changing foreign partnership characteristics: a model of dynamic technology management strategies. (1st January 2013) - Nakandala, Dilupa; Turpin, Tim
This article investigates the technological development process in local firms in joint venture partnerships with foreign firms. It takes the perspective of the local firms located in a developing economy and presents a model of dynamic technology management strategies (MDTMS) of local firms for sustained technological development. Based on an analysis of six firms from the rubber products and garment accessories manufacturing in Sri Lanka, it reveals how the level of skills and competence development within the local firm, the potential for technological contribution by the foreign partner firm and the level of autonomy of the local firms are important determinants for shaping technology management strategies. It argues that these successful Sri Lankan firms adopt dynamic technology management strategies because of the evolving nature of the partnership. The proposed model has significant implications for the technology management practices of local firms in developing economies that engage in foreign partnerships.